Electrostatic self-assembly of LiFePO4 cathodes on a three-dimensional substrate for lithium ion batteries. (1st September 2018) - Tian, Guiying; Scheiba, Frieder; Pfaffmann, Lukas; Fiedler, Andy; Chakravadhanula, Venkata Sai Kiran; Balachandran, Geethu; Zhao, Zijian; Ehrenberg, Helmut
Abstract: In this work, the electrostatic self-assembly of LiFePO4 particles coated with polyelectrolytes on a three-dimensional carbon substrate is described. This new fabrication method allows precise control of ionic and electronic conduction pathways as well as the interfaces between the different electrode components, thus enabling new strategies for tailored electrode designs. Further, it is shown that the polyelectrolytes used to build up the electrode by electrostatic self-assembly can be converted into a conductive matrix by a simple carbonization step. This leads to a firmly adhering carbon film on the surface of LiFePO4, which further improves electron transport. The three-dimensional composite cathode exhibits a high specific capacity even at high current rates as well as a long cycle life. The excellent electrochemical performance can be attributed to the improved three-dimensional structure of the electrode as well as to the obtained intrinsic carbon coating of LiFePO4 particles. Graphical abstract: A binder-free hollow-LiFePO4 /carbon-cloth composite cathode prepared via electrostatic self-assembly of polyelectrolytes displays superior rate capacity at high current density, demonstrating a promising way to use the electrostatic self-assembly to prepare 3D electrodes. Image 1 Highlights: The combination of carbon cloth and composite LFP/carbon via electrostatic self-assembly to fabricate a 3D cathode. The successful preparation of LFP hollow nanoparticles via a hydrothermal process. A binder-free LFP/carbon cathode obtained through polyelectrolyte electrostatic self-assembly and afterwards carbonization. An enhanced electronic/ionic conductivity due to carbon coating on the LFP hollow particles with self-supporting substrate.